Entity Management Responsibility in Implementing the Internal Audit Recommendations: Array - Ardeleanu (Trifu), Nicoleta; Bogasiu (Anton), Isabela-Raluca (Journal of Danubian Studies and Research, 2021)
The public entities in Romania, in the last 20 years, have known a change of concept between the financial management control organized over the financial-accounting operations and the internal public audit exercised over all general and specific objectives, those forecast. The object of the research is the reporting of the results and the opinion of the audit, of the way of implementing the recommendations formulated towards the internal control instruments adopted at the level of the public entity.